Surgical Repair of Retrograde Type A Aortic Dissection after Thoracic Endovascular Aortic Repair - Kim, Chang-Young (Korean Society for Thoracic and Cardiovascular Surgery, 2014)
It is expected that the stent graft will become an alternative method for treating aortic diseases or reducing the extent of surgery; therefore, thoracic endovascular aortic repair has widened its indications. However, it can have rare but serious complications such as paraplegia and retrograde type A aortic dissection. Here, we report a surgical repair of retrograde type A aortic dissection that was performed after thoracic endovascular aortic repair.